RESEARCH AND COLLECTION OF VEGETABLE AND CUCURBIT CROP GENETIC RESOURCES IN THE TERRITORY OF KYRGYZSTAN IN 2014 - D. L. Kornyukhin; G. V. Talovina (Труды по прикладной ботанике, генетике и селекции)
A collecting mission over the territory of Kyrgyzstan was carried out in 2014. The goal of that mission was searching for wild relative species of spinach, Spinacia turkestanica Iljin, and collecting of samples of this species. Also, collecting of vegetable crops and cucurbits as well as wild relative species of such crops was important. As a result, 49 samples of wild spinach were collected in its native habitats. Most frequently wild spinach grows in the agricultural zone of foothill regions of the Chuy and Fergana Valleys. A map of all collecting sites of S. turkestanica was made. Typical habitats of wild spinach were ruderal places and agrophytocenoses. Also, a set of wild spinach satellite species was detected. Besides, 116 samples of vegetable crops and cucurbits were purchased at the local markets; six samples of wild onion (Allium sp.) were collected in natural environments.